Application fuzzy DEMATEL methodology to investigate some technical parameters of biochemical methane potential (BMP) test produced vegetable waste anaerobic biogas - Bashan, Veysi; Cetinkaya, Afsin Y. (Springer, 2022)
As the transition to renewable energy systems is accelerating, anaerobic digestion, which is one of the methods of energy recovery from organic substrates, continues to be studied with great interest by scientists. Anaerobic digestion research and applications are mostly carried out with biochemical methane potential (BMP) tests to decide the methane potency of sewage sludge, energy crops, and organic wastes. Unlike long and costly continually reactor experiments, actually, BMP tests are cumulative and can be performed with a relatively low investment of materials, technical labor, and also time. For the BMP to give accurate results, the effect of all the tools and technical parameters used in the implementation of the BMP should be well understood. In such situations, it is very useful to apply fuzzy logic methods in multi-criteria decision-making stages when more than one parameter changes at the same time. Therefore, in this study, fifteen parameters were determined and analyzed with the fuzzy DEMATEL (decision-making trial and evaluation laboratory) method to understand the cause-effect mechanism of the technical parameters of BMP. As a result of these analyses, it was seen that the material of the reactor (r(i)-c(j) value of 0.55), the particle size (r(i)-c(j) value of 0.43), the effect of mixing (r(i)-c(j) value of 0.32), and the amount of the total solids (TSA) value of 0.25) had a high effect in the causal sense. It was observed that the first-order parameter (material of reactor) was 27% stronger than the second-order (the particle size) parameter in terms of causality. Likewise, the second-order parameter is 34% stronger than the third-order parameter (the effect of mixing) in terms of cause effect. In addition, it was understood that the most effective parameters in the mechanism of effect were pH (r(i) +c(j) value of 3.41), C/N ratio (r(i)-c(j) value of 3.26), and temperature (r(i)-c(j) value of 3.07), respectively. Besides, high methane yield is seen in mesophilic conditions. The average cumulative biogas yield of the reactor is 282.1 NmL/g VS. The highest percentage of methane formed in the biogas occurred on the 21st day. Briefly, this study is important to provide a facilitating way for researchers working on BMP to understand the causeeffect mechanism of system technical requirements.
Keywords: Biochemical methane potential; BMP; Vegetable waste; Fuzzy DEMATEL